2020
DOI: 10.1002/jip.1547
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness of adult and juvenile prisoner influences on psychological affect: Mediation role of control source

Abstract: Prisoners' affective education is a hot topic in criminal psychology. The lack of the social support for prisoners means that they are more prone to loneliness. The mental health status of the prisoners directly concerns their social adaptation when released. We therefore explored the relationship between loneliness, psychological affect, and control source in 201 prisoners. Prisoners completed the state and trait loneliness scale, the affectal scale, the internal control, powerful others, and chance scale. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In addition, prisoners with a feeling of loneliness were found to have lower levels of self-esteem (Coticchia and Putnam, 2021), increased behavioural and health problems and maladaptive ways of coping with stress (Jozan, 2020). Another study on the relationship between loneliness and psychological effects in both adult and juvenile prisoners in China found that loneliness due to a lack of social support in the prison was directly and significantly associated with poor mental health status (Zhao and Shi, 2020). This explains why participants in our study connected the feeling of loneliness with the experiences of mental health problems and lack of well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prisoners with a feeling of loneliness were found to have lower levels of self-esteem (Coticchia and Putnam, 2021), increased behavioural and health problems and maladaptive ways of coping with stress (Jozan, 2020). Another study on the relationship between loneliness and psychological effects in both adult and juvenile prisoners in China found that loneliness due to a lack of social support in the prison was directly and significantly associated with poor mental health status (Zhao and Shi, 2020). This explains why participants in our study connected the feeling of loneliness with the experiences of mental health problems and lack of well-being.…”
Section: Discussionmentioning
confidence: 99%